Has The Roles Been Changed? Preschool Children’s Views About Social Gender Roles - Unlüer, Esra; Öncü, Elif Çelebi (Southeast Asia Early Childhood Journal, 2022)
The World is changing very rapidly so did the views, perceptions and roles in gender based activities and responsibilities, new terms such as gender fluency, gender variant, transgender etc. has been seen in latest research and articles.  The aim of this study is to reveal the perceptions of children in early childhood on gender roles. To that end, first of all, children's perceptions were scrutinized in view of gender constancy and invariance according to age and gender. Secondly, the perceptions of children were examined in terms of gender-based division of labor and gender-based occupations were examined. Attaining 4 different free preschool institutions in the central district of Kocaeli province 251 children who are 3, 4 and 5 years old participated in the study, all having parental permission. The measurement tools used in the study were developed by the researchers. Firstly, gender specific accessories and toys to be used in relation to gender constancy, the daily routines that people frequently perform and occupations were determined. Twelve different animals were selected to prevent the emergence of gender-based bias in children on daily works and occupations. These animals were matched with the predetermined 6 daily works and 6 occupations and they were depicted in pictures while performing daily works and occupations. In addition, the identified accessories, toys and situations are depicted in black and white to prevent the formation of color wise gender-based bias. According to the findings of the study, it was seen that children in the 3-year-old group had lower gender conservation gains compared to children amongst the other-age groups. It was seen that in all of the three age groups, regardless of their gender, the majority of children expressed gender-based judgmental views about daily routines and occupations.